Four new species of Luciuranus fireflies from the Brazilian Atlantic Rainforest (Coleoptera: Lampyridae) - Silveira, Luiz F. L. Da; Souto, Paula M.; Mermudes, J. R. M. (Zootaxa, 2018)
Luciuranus Silveira, Khattar & Mermudes, 2016 is a firefly genus whose species bear an intricate, species-specific lock-and-key mechanism of reproductive isolation. Here we propose four new species, Luciuranus magnoculus sp. nov., L. desideratus sp. nov., L. takiyae sp. nov. and L. carioca sp. nov., and provide illustrations of their diagnostic features and an updated key to species. As previously reported for their congenerics, each of the four new species have stereotypical morphology of both male and female terminalia, and are regarded as prima facie endemics of single massifs of the Serra da Mantiqueira and Serra do Mar, in the Brazilian Atlantic Rainforest.